Regional variations and spatial heterogeneity of lumbar CT attenuation are associated with osteoporotic vertebral fracture - Cai, Jinhui; Chen, Ludan; Liu, Long; Yi, Jinsheng; Wu, Jiaqi; Yang, Tingqian; Huang, Wensheng; Liu, Qingyu (Frontiers in Endocrinology, 2025)
SummaryOsteoporotic vertebral fracture (OVF) constitutes a prevalent health concern in the elderly. Reduced vertebral HU values and increased spatial heterogeneity in the L1 and L2 vertebrae were independently associated with OVF. The HU values combined with spatial heterogeneity quantification could be a feasible approach for opportunistic OVF risk assessment.PurposeExamine the associations between vertebral Hounsfield units (HU) and osteoporotic vertebral fracture (OVF), with a particular emphasis on regional variations and spatial heterogeneity of vertebral trabeculae.MethodsThe regional (anterior, middle, posterior, superior, inferior) and total HU in L1 and L2 vertebrae were measured, and with spatial distribution quantified through regional HU ratios. Heterogeneity in HU were assessed using interquartile range (IQR) and coefficient of variation (CV). Group differences were analyzed by Mann-Whitney U test and t-test, while multiple comparisons of CT measurements were adjusted using the Benjamini-Hochberg (B-H) method. Logistic regression identified independent factors associated with OVF, and ROC curves evaluated the diagnostic efficacy of vertebral HU for vertebral fracture prediction.ResultsThis retrospective case-control study comprising 54 individuals with acute OVF and 108 age- and sex-matched controls. The regional and total HU of L1 and L2 (B-H adjusted p< 0.001) decreased in OVF patients compared to the controls. The OVF patients exhibited higher CV in both L1 and L2, and CV (per 10% increased) were positively associated with increased odds of OVF independent to vertebral HU and T-score (L1: adjusted OR 2.845; 95% CI, 1.076 - 7.524; p= 0.035 and L2: adjusted OR 2.944; 95% CI, 1.246 - 6.955; p= 0.014). ROC revealed moderate predictive accuracy for total vertebral HU (L1: AUC = 0.715; L2: AUC = 0.738), with marginally superior performance in inferior regions (L1: AUC = 0.716; L2: AUC = 0.740).ConclusionReduced vertebral HU values and increased spatial heterogeneity in L1 and L2 vertebrae were associated with OVF, providing valuable references for OVF risk assessment.